"In vitro" evaluation of some properties in spore former bacteria isolated from calves faeces - Maldonado, Natalia Cecilia (2015)
Aims: To isolate and evaluate spore-former bacteria for being used as probiotic additives in animal nutrition by their technological features. Study Design: The study was experimental, by using calves’ faeces for spore-forming identification and further evaluation of their “in vitro” probiotic-related properties. Place and Duration of Study: Laboratory of Preventive Microbiology, Centro de Referencia para Lactobacilos (CERELA-CONICET), between June 2013 and November 2013. Methodology: In this work, some Bacillus strains were isolated from calves’ faeces and evaluated for their “in vitro” beneficial characteristics: Surface properties, biosurfactant and emulsification production, and inhibition of pathogens. The antibiotic sensibility was also assayed. Results: Two Bacillus strains were selected, identified by phenotypic and molecular techniques as Bacillus subtilis strains M14 and M12. Spores resulted to be more hydrophobic than vegetative cells. The M14 strain showed biosurfactant and emulsifying properties. Inhibition assays against pathogenic bacteria indicated they inhibit gram-positive microorganisms. The antibiotic susceptibility showed that the two strains were sensitive to the antibiotics assayed, except Bacillus M12 that was resistant to Kanamycin. Conclusion: The results indicate these strains can be further studied for their inclusion in the design of a probiotic product for newborn calves.